Code-to-code SIMMER/FRENETIC comparison for the neutronic simulation of lead-cooled fast reactors. (1st September 2022) - Massone, Mattia; Abrate, Nicolò; Nallo, Giuseppe Francesco; Valerio, Domenico; Dulla, Sandra; Ravetto, Piero
Abstract: This paper presents a neutronic benchmark between the FRENETIC and the SIMMER codes, performed considering the core of the ALFRED lead-cooled fast reactor. FRENETIC includes a nodal diffusion module developed for fast full-core analyses of safety-relevant transients in liquid-metal fast reactors, while SIMMER is a reference tool for qualifying such kind of systems in accidental conditions. In order to highlight the influence of the different numerical methods available in the two codes on the output responses, macroscopic parameters like the effective multiplication factor and the linear power are compared in an increasingly detailed simulation framework. The 3D full-core FRENETIC results are compared at first to a cylindrical 2D SIMMER core model, to highlight the impact of the absorber rings location. Then, a 3D full-core model is also employed in SIMMER to assess the differences, with respect to FRENETIC, induced by the adoption of a Cartesian mesh and of the discrete ordinates method. The full input data consistency is ensured providing the same set of few-group material constants, generated with the Monte Carlo code Serpent 2. Finally, the W- ε scheme is applied to accelerate the angular and spatial convergence of the k eff sequences computed by SIMMER in order to estimate the asymptotic errors with respect to the reference Serpent calculation.